Modeling of masonry structures using a new 3D cohesive interface material model considering dilatancy softening. (15th February 2023) - Li, Yong; Zeng, Bowen
Highlights: A 3D multi-yield surfaces constitutive model for interface element is developed for mortar joints. The dilatancy softening is incorporated into an unassociated flow rule to accurately capture the dilatancy behavior. Implicit Backward integration, combined with a sub-stepping strategy is applied to achieve the numerical robustness, efficiency, and accuracy. The developed constitutive model is validated at various scales to show its applicability. Abstract: This study presents a new 3D multi-yield surfaces material model for masonry mortar joints, which can be used with interface elements for finite element (FE) modeling of masonry structures to capture various failure mechanisms. This model is featured with (1) two hyperbolic yield surfaces, capable of capturing various failure modes of mortar joints, including tensile cracking, shear sliding, and compressive crushing, (2) an unassociated flow rule to capture the 'dilatancy' phenomenon in the mortar joints, and (3) the dilatancy softening and variation of mode II fracture energy under different normal stress levels. An implicit Euler backward integration algorithm, combined with local-global Newton-Raphson (NR) solver, is adopted to achieve the predictor-corrector return mapping in the numerical formulation. The error-based auto-adaptive sub-stepping algorithm is employed to achieve the robustness and efficiency in the integration procedure. The developed model is implemented in the general-purpose FE software ABAQUS with the specialized capability of modeling masonry structures. The developed model is validated through three brick-mortar-brick assemblages and three un-reinforced masonry (URM) walls under in-plane (IP) loading or out-of-plane (OOP) loading. The importance of appropriate modeling of dilatancy on simulating the IP and OOP behavior of URM walls is highlighted. The validation results show that the developed constitutive model is capable of modeling masonry structures at various scales with improved accuracy by considering dilatancy softening.